Investigation of the Effect of Bedding Layer Angle and Tunnel Number on the Stability of Tunnel under Uniaxial Compression Using PFC2D - Sarfarazi, Vahab; Asgari, Kaveh; Azizian, Mahdiyah (Periodica Polytechnica Civil Engineering, 2021)
In this paper the effect of bedding layer angle on the stability of tunnel under uniaxial compression have been investigated using particle flow code in two dimensions (PFC2D). For this purpose, numerical rectangle models with dimension of 100*100 mm have been prepared. These models consist of layers with different mechanical properties i.e., concrete layer and gypsum layer. The angle of these layers related to horizontal axis change from 0° to 90° with increment of 15°. These models are consisting of one, two and three tunnel. The diameter of tunnel change based on the tunnel number. The tunnel diameter was 6 m, when one tunnel exists in the model. The tunnel diameter was 3 m, when two tunnels exist in the model. The tunnel diameter was 2 m, when three tunnels exist in the model. These models were subjected to uniaxial compression. The results show that tensile cracks are dominant mode of fracture occurred in the models. The joint angle and tunnel number have important effect on the failure pattern and failure strength. Also, the mechanical properties of beddings control the crack growth path. The crack grows through the weak layers when bedding angle was equal to 45° and 60°, but it intersects the layer for any other bedding angels.